Labour market, welfare reform and inequality in the United Kingdom - André, Christophe; Garcia, Clara; Giupponi, Giulia; Pareliussen, Jon Kristian (Paris, 2013)
"Employment has risen by more and unemployment has risen less than expected, given the path of output. Nevertheless, long-term and youth unemployment and involuntary part-time work are high. A polarised labour market risks worsening income inequality, which is high by OECD standards, despite a recent and likely temporary decline. The UK welfare system is an essential safety net, which needs to promote employment, while protecting the most vulnerable. The reformed welfare system, Universal Credit, and the employment programme for disadvantaged workers, Work Programme, will generally improve work incentives and provide support for return to work, but need to be refined. Skill deficiencies are holding back employment and fostering inequality, as low education achievements penalise children from lower socio-economic backgrounds. Vocational training needs to be strengthened and cooperation with employers reinforced. Transition from education to work can prove challenging, requiring more attention to the integration of university graduates into the labour market."